THE INFLUENCE OF SPIRITUAL INTELLIGENCE ON STUDENTS' DISCIPLINE ATTITUDES AT AL-ISTIQAMAH MODERN ISLAMIC BOARDING SCHOOL NGATABARU - Nurhidayanti, Nurhidayanti; S. Pettalongi, Sagaf; Erniati, Erniati; Jumri Hi Thahang Basir; Anirah, Andi (Department of Islamic Education, Postgraduate Program Univercity for Islamic Studies Palu, 2024)
This study examines the Influence of Spiritual Intelligence on Students' Discipline Attitudes at Al-Istiqamah Modern Islamic Boarding School Ngatabaru. The study used a qualitative approach with descriptive techniques for presenting data from informants. Data were collected through observation, in-depth interviews, and document analysis. The analysis process involved data reduction, presentation, verification, and conclusion drawing. This stdy foun that spiritual intelligence is an essential ability for students that influences other intelligence, including discipline. Students with spiritual intelligence will be more easily motivated to follow the rules and carry out the rules of the Islamic boarding school. Life at the Al-Istiqamah Ngatabaru Modern Islamic Boarding School is regulated by strict regulations that include various activities, from the five daily congregational prayers and greetings to a structured daily schedule. Discipline in praying is not only required as a pillar of Islam but also as a builder of character and spiritual intelligence. Practices such as greeting each other are also instilled as a form of respect that supports discipline and noble morals